(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
Public Sociology as Educational Practice frames, critically engages with and seeks to further the theory and practice of public sociology as popularised by public sociologist, Michael Burawoy. Public sociology is about taking sociology outside the university, and using it to support ‘publics’ or communities to generate knowledge about society and how it can be changed. To readers of a journal about community education this aim will likely sound familiar; the explicit and implicit links between arguments for public sociology and the dialogical pedagogy of Paulo Freire are clear throughout the book.